Renal bone disease in patients on hemodialysis: an observational study focusing on the variation of calcium metabolism - Elahi, Wajeeha; Syed, Ameen Zubair; Jamil, Bilal; Kamran, Shahid; Adil, Raheela; Qamar, Nazia; Ariff, Madiha; Anwar, Adnan (International Journal of Research in Medical Sciences, 2019)
Background: The aim of this study was to determine the disturbances in the levels of mineral in the body due to hemodialysis at different levels of parathormone levels and to assess its association with the calcium levels. Methods: Study was a cross sectional for the period of 6 months taking ethical approval. Total 255 cases were registered in this study after taking their informed consent. The cases were divided into three groups according to PTH level. Group 1 has 87 subjects with PTH level <250, group 2 has 102 subjects with PTH level 250-650 and group 3 has 66 cases with PTH level >650. The cases were taking hemodialysis for greater than 6 months and have the ages more than 18 years were included in this study. The demographic data includes age, sex dialysis related data like duration of hemodialysis, levels of calcium, phosphorus, albumin, PTH, ALP were observed. Results: Hemodialysis duration were recorded in respective three groups as 7.28±5.71, 6.26±5.56 and 6.15±4.30 days respectively (P=0.319). Calcium was found in group 1, 8.70±0.81, in group 2, 8.39±0.89 and in group 3, 8.76±0.82 (P=0.01). PTH level in three respective group were recorded to be 123.46±74.15, 418.47±115.49 and 1314.67±1188.63 (P <0.001). Conclusions: Present study showed that significant difference was found in mineral levels in patients on hemodialysis with PTH level as well as with alkaline phosphatase level. Nevertheless, no significant difference was found with duration of dialysis and with parameter of albumin.